The Role of Self-Leadership in Public Health: Controversies in Stunting Prevention Efforts by Village Development Non-Commissioned Officers (Babinsa) - Muryanto; Ratminto Ratminto; Hakimul Ikhwan; Umi Listyaningsih (Asian Journal of Social and Humanities, 2026)
Stunting is a significant health problem in Indonesia, particularly in rural areas. This study emphasizes the self-leadership of Babinsa (village supervisory non-commissioned officers)—as street-level actors—in stunting prevention in Indonesia. It aims to explore the role of village development non-commissioned officers (NCOs) of the Indonesian National Armed Forces (TNI), known as Babinsa, in stunting prevention efforts by examining how a self-leadership model can enhance their effectiveness in addressing this public health challenge. This study used a qualitative approach with a case study design, focusing on Babinsa in Magelang Regency, Central Java. Data were collected through in-depth interviews with key informants, including Babinsa, Posyandu cadres, village midwives, village officials, and families of stunting sufferers. Thematic analysis was used to identify key themes and insights from the data. The findings revealed that Babinsa (village-based non-commissioned officers) who applied self-leadership principles demonstrated increased adaptability in implementing stunting prevention strategies tailored to community needs. However, challenges such as bureaucratic constraints and limited resources impacted the effectiveness of these efforts. Collaboration between Babinsa, health workers, and community members proved crucial for successful interventions, highlighting the importance of cultural sensitivity and community engagement. The study concluded that implementing a self-leadership model by Babinsa could significantly improve their effectiveness in stunting prevention. Insights from this study can inform policymakers and practitioners in designing better training programs and support systems to reduce the prevalence of stunting in Indonesia.